Module for measuring gender norms in agrifood systems: Adapted for focusing on youth and mechanization in Bangladesh - Heckert, Jessica; Mahzab, Moogdho; Quisumbing, Agnes R.; Simi, Sonjida Mesket (International Food Policy Research Institute, 2025)
This module is designed for use in agricultural communities in Bangladesh. Specifically, we expect that it will be well suited for evaluating changes in gender norms for gender transformative approaches paired with technical interventions with an agricultural mechanization component.